2018
DOI: 10.1002/cam4.1611
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy after curative surgery for oral cavity squamous cell carcinoma and treatment effect of timing and duration on outcome—A Taiwan Cancer Registry national database analysis

Abstract: Conduct an accurate risk assessment of resected oral cavity squamous cell carcinoma (OSCC) patients by accessing a nationwide systemic investigation is pivotal to improve treatment outcomes. In this article, we tried to determine the impact of different prognostic factors for OSCC patients who received adjuvant radiotherapy (RT) after curative surgery, using Taiwan's national cancer registry database (TCR). A nationwide, large population‐based study was conducted using TCR with patients identified from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…This is according to current recommendations [35], and was a positive finding, as these patients were treated nine to 14 years ago when MDT meetings were less established than today. Cancer in the oral cavity is normally managed by surgical removal of the primary tumor, sometimes combined with neck dissection and/or RT, while chemotherapy is seldom used [28][29][30][31][32][33][34]. The same standard of treatment was also found in our cohort.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is according to current recommendations [35], and was a positive finding, as these patients were treated nine to 14 years ago when MDT meetings were less established than today. Cancer in the oral cavity is normally managed by surgical removal of the primary tumor, sometimes combined with neck dissection and/or RT, while chemotherapy is seldom used [28][29][30][31][32][33][34]. The same standard of treatment was also found in our cohort.…”
Section: Discussionmentioning
confidence: 58%
“…Primary surgery is the preferred treatment for oral cavity squamous cell carcinoma (OCSCC) in most institutions when the tumor is regarded resectable, with or without reconstruction and neck dissection. Postoperative adjuvant radiation therapy (RT) is often necessary, whereas chemotherapy is seldom used, except sometimes for advanced stages [28][29][30][31][32][33][34]. The treatment should be decided by a multidisciplinary team (MDT) [35].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that males over the age of 70 years with tongue cancer who received the standard of care (surgery þ adjuvant radiation therapy) had poorer locoregional recurrence-free survival, overall survival, and response to adjuvant radiation compared with younger patients. 2 In conclusion, the findings from Lin et al identify a subgroup of patients with locoregionally advanced oral cavity SCC who may be optimally treated by surgery alone with good local control and very good disease-specific and overall survival. In light of the well-known caveats of retrospective studies, we cannot recommend deintensification of this cohort as the standard of care at this time.…”
mentioning
confidence: 84%
“…Adherence to the initially prescribed RT regimen is paramount to ensure optimal treatment outcomes, and deviations from the initial schedule may have adverse prognostic implications. In this context, published studies have shown that several variables related to the RT scheduleincluding length of radiation time, premature discontinuation of RT, and time to initiation of postoperative RTpredict prognosis in patients with head and neck malignancies [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%